ARABICA COFFEE CULTIVARS IN DIFFERENT WATER REGIMES IN THE CENTRAL CERRADO REGION - Veiga, Adriano Delly; Rodrigues, Gustavo Costa; Rocha, Omar Cruz; Bartholo, Gabriel Ferreira; Guerra, Antônio Fernando; da Silva, Thiago Paulo (Coffee Science - ISSN 1984-3909, 2019)
Phenotypic characterization of coffee cultivars under an irrigation system, as well as adaptability to controlled water stress, aiming at flowering uniformity, high yield and grain quality, plays an important role in coffee production in the cerrado areas. A field trial was carried out aiming to evaluate the agronomic performance of arabica coffee cultivars under different water regimes, using center pivot irrigation: irrigation throughout the year (WR1); suspended at the end of June for 40 days until leaf water potential reached -1.5 MPa (WR2); suspended at the end of June for 70 days until leaf water potential reached -2.3 MPa (WR3); suspended at the end of June for 100 days until leaf water potential reached -3.4 MPa (WR4); and a non-irrigated regime (WR5). The following traits were analyzed: plant height, stem diameter, canopy projection, number of plagiotropic branches, coffee grain yield, percentage of fruit in the cherry stage, and sieve retention percentages. Higher yield, plant growth, and percentage of fruit in the cherry stage are observed in the water regime with seventy days of controlled water stress (WR3). The Obatã IAC 1669-20 cultivar exhibits high yield and plant growth values in an irrigated system, and Catuaí Amarelo IAC 86 stands out in the non-irrigated system. For these genotypes, the coffee grain yield is most highly correlated with number of reproductive branches.